(untitled) (Baghdad Science Journal, 2025)
Cancer stay to be one of the leading causes of death throughout the world due to a limited success to use treatments. The new synthesized metal complexes with formula: [Ni L2 (H2O)2]. 2.5 E t OH and [Cd L2]. ½ H2O Where L = Bis [ 5 – ( P – nitrophenyl ) - 4 – phenyl 1 , 2 , 4 – trazol – 3 – dithiocarbamato hydrazide ] and the aqueous extract of Teucrium polium L.(TP) plant (Ja,adahin Arabic) were examined against growth cells of hepatocellular Carcinoma cell Line ( HeP2 ). The cytotoxicity assay of cancer cell line was used for determination of inhibition rate with three concentrations; (62.5, 105 and 250 µg /200µl). The aqueous extract of TP plant induced death of cancer cells by significant elevation of the inhibition rate to 50.03% while the cytotoxic effect of Ni ( II ) complex reached 45.77% and Cadmium (II) was 35.73% at 125µg /200µl.The present study indicates that there are no significant differences between the two new complexes Nickel(II) and Cadmium(II) compared with anticancer drug Cis-pt for all doses